Notes on Ricardo's intellectual complicity Palma and Juana Manuela Gorriti - Holguín Callo, Oswaldo (2019)
A dear friendship existed between Ricardo Palma and Juan Manuela Gorriti, one that lasted for more than four decades. She was fifteen years his senior and guided the young bohemian man in his first literary essays. He truly appreciated her narrative work and considered her a part of the Peruvian parnassus. This article develops some chapters of a friendship that was also considered a complicity in cultural and journalistic ventures such as the well-known literary evenings in Lima in 1876 and 1877.